2019
DOI: 10.3390/microorganisms7050137
|View full text |Cite
|
Sign up to set email alerts
|

Shiga-Toxin Producing Escherichia Coli in Brazil: A Systematic Review

Abstract: Shiga-toxin producing E. coli (STEC) can cause serious illnesses, including hemorrhagic colitis and hemolytic uremic syndrome. This is the first systematic review of STEC in Brazil, and will report the main serogroups detected in animals, food products and foodborne diseases. Data were obtained from online databases accessed in January 2019. Papers were selected from each database using the Mesh term entries. Although no human disease outbreaks in Brazil related to STEC has been reported, the presence of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 108 publications
1
28
0
1
Order By: Relevance
“…STEC have been associated with foodborne disease outbreaks worldwide (Castro et al 2019;Heredia and García 2018). The biofilm-forming potential of non-O157 STEC on stainless steel have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…STEC have been associated with foodborne disease outbreaks worldwide (Castro et al 2019;Heredia and García 2018). The biofilm-forming potential of non-O157 STEC on stainless steel have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in Kenya also indicated the low prevalence (0.2%) of E. coli O157: H7 in hospitalized diarrheic children ( 21 ). But in some countries high prevalence rate of STEC was reported, Ifeanyi in Nigeria ( 22 ) and Dambrozio in Brazil (2014) ( 23 ) identified EHEC pathotypes in 12.6% and 21.2% of children with diarrhea, respectively. Pourakbari et al (2013) studied 50 children with diarrhea and 50 healthy ones referring to a medical center in Iran, E. coli was isolated in 90% of patients and 20% of healthy controls, also, EHEC strains were identified in 14% and 3% of patients and controls, respectively ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Castro et al wrote a systematic review on STEC in Brazil by selecting papers from online databases (according to Prisma guidelines), and limiting their search for articles published between January 2000 and December 2018 [1]. Collecting data produced by others is not an easy task; and the authors should be very cautious when making statements and concluding remarks that are not supported by the selection of references and parameters used.…”
mentioning
confidence: 99%
“…Moreover, in an attempt to explain that there were no reports of outbreaks involving STEC, Castro et al [1] stated two untrue hypotheses “(i): Disease outbreaks are not recorded by lack of centralized reporting system or (ii) disease outbreaks are not being recognized as there are no surveillance systems for STEC ”. In fact, in São Paulo, the active surveillance of HUS, bloody diarrhea, and E. coli are part of the active surveillance system for foodborne diseases (DTA), the Monitoring of Acute Diarrheal Diseases (MDDA), and the surveillance of outbreaks of DTA [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation